A New Prognostic Algorithm Predicting HCC Recurrence in Patients With Barcelona Clinic Liver Cancer Stage B Who Received PA-TACE - Hu, Shuyang; Gan, Wei; Qiao, Liang; Ye, Cheng; Wu, Demin; Liao, Boyi; Yang, Xiaoyu; Jiang, Xiaoqing (Frontiers in Oncology, 2021)
Background: Postoperative adjuvant transcatheter arterial chemoembolization (PA-TACE) is effective in preventing the recurrence of hepatocellular carcinoma (HCC) in patients treated with surgery. However, there is a lack of reports studying the risk factors associated with recurrence in HCC patients who received PA-TACE. In this study, we identified the independent risk factors for recurrence of HCC patients who received PA-TACE. We also developed a novel Nomogram to predict the individual probability of recurrence, 1-, 3-, and 5-years after PA-TACE. Methods: A retrospective study was performed to identify the independent risk factors for recurrence of HCC in a group of 502 patients diagnosed in stage B based on the Barcelona Clinic Liver Cancer (BCLC) evaluation system for HCC that underwent curative resections. Then, subgroup analysis was performed for 184 patients who received PA-TACE, who were included in the training cohort. The other 147 HCC patients were included in a validation cohort. A recurrence free survival (RFS)-predicting Nomogram was constructed and results were assessed using calibration and decision curves as well as a time-dependent AUC diagram. Results: PA-TACE was shown to be a significant independent prognostic value for patients with BCLC stage B (P<0.001, HR=0.508, 95%CI=0.375-0.689 for OS, P=0.002; HR=0.670, 95%CI=0.517-0.868 for RFS). Alpha fetoprotein (AFP), tumor number, tumor size, microvascular invasion (MVI) and differentiation were considered as independent risk factors for RFS in the training cohort and these were further confirmed in the validation cohort. Next, an Nomogram was constructed to predict RFS. The C-index for RFS in the Nomogram was 0.721 (95%CI=0.718-0.724), which was higher than SNACOR, HAP and CHIP scores (0.587,0.573 and 0.607, respectively). Calibration and decision curve analyses as well as a time depended AUC diagram were used. Our Nomogram showed stronger performance than these other Nomograms in both the training and validation cohorts. Conclusions: HCC patients diagnosed as stage B according to BCLC may benefit from PA-TACE after surgery. The RFS Nomogram presented here provides an accurate and reliable prognostic model to monitor recurrence. Patients with a high recurrence score based on the Nomogram should receive addition high-end imaging exams and shorter timeframes in between follow-up visits.